Cerebral Abscess Following Endovascular Treatment of Aneurysm: Report of 2 Cases and Review of the Literature - (:unkn) unknown (ELSEVIER SCIENCE INC, 2019)
INTRODUCTION: Endovascular treatment is growing in popularity globally as an important treatment option for intracranial aneurysms. Cerebral infection as a complication of endovascular treatment of aneurysms is sufficiently rare that only 6 isolated cerebral abscess cases have been reported thus far. CASE REPORT: In this report, we present 2 cerebral abscesses from 3 institutions, which developed after coil embolization of anterior communicating artery and middle cerebral artery aneurysms. CONCLUSION: This report was written to discuss the possible mechanisms underlying cerebral abscess after endovascular treatment of aneurysms and to suggest potential treatment and prevention methods.
Keywords: Cerebral abscess; Cerebral aneurysm; Coil excision; Endovascular embolization; Infection; GUGLIELMI DETACHABLE COILS; BRAIN-ABSCESS; SACCULAR ANEURYSM; EMBOLIZATION; COMPLICATION; INFLAMMATION; BACTEREMIA; EDEMA; RISK